A new training load quantification method at supra-maximal intensity and its application in injuries among members of an international volleyball team - Bouzigues, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In volleyball (VB), the quantification of the training load (TL) is based on the number of jumps (Piatti et al., 2021), however the jump height is not considered. The repetition of intense jumps is source of significant mechanical stress and promote the injury occurrence (Bahr and Bahr, 2014). To optimize jump performance and reduce the occurrence of injuries, it`s necessary to monitor and quantify specifically TL in VB (Debien et al., 2018). The aims of this study were (i) to propose a new method for quantifying TL for explosive exercises, (ii) to determine the nature of the relationships between the dynamics of TL and injury occurrence and (iii) to find a limit TL in terms of jumps, above which the risk of injury occurrence become unacceptable, for optimizing the training schedule.